Palm Seed Insole Innovation for Alleviating Foot Numbness among Patients with Diabetes - Suwannarat, Piyanuch; Prom-in, Supattra; Aumpama, Benjawan; Noipha, Kusumarn (Public Health of Indonesia, 2025)
Background: Previous reviews have demonstrated the effectiveness of Thai reflexology massage in alleviating symptoms of diabetic neuropathy. However, there remains a notable gap regarding its long-term sustainability and ease of implementation. To address this issue, the Palm Seed Insole Innovation has been proposed as a practical alternative, offering benefits such as self-administration and accessibility. Nonetheless, comprehensive research including clinical trials and economic evaluations is essential to validate the efficacy and safety of this innovation. Objective: The objectives of this study were to develop a reflexology massage tool, evaluate the effectiveness of the palm seed insole innovation in improving foot sensation among individuals with diabetes, and assess user satisfaction with the innovation. Methods: This study employed a single-group pre-test and post-test design to assess the impact of self-administered foot massage using palm seed insoles on foot numbness among individuals aged 40–70 years diagnosed with type 2 diabetes. A purposive sampling method was used to recruit 35 participants who experienced peripheral foot numbness. Participants performed self-foot massage using the insoles for approximately 15 minutes, three times per week, over a four-week period. After the intervention, user satisfaction with the innovation was measured. Data were analyzed using descriptive statistics (percentages, means, standard deviations) and inferential statistics (paired t-tests). Results: The findings indicated a statistically significant improvement in foot sensation following the four-week intervention (p = 0.000). The mean numbness score for the right foot decreased from 1.71 to 0.60, while the score for the left foot decreased from 2.09 to 0.60. Furthermore, participants reported a high level of satisfaction with the use of the palm seed insole in reducing diabetic neuropathy symptoms. Regarding the innovation’s design, the satisfaction score averaged 4.49 with a standard deviation of 0.76, indicating a positive user experience. Conclusion: The study concluded that self-administered foot massage using the palm seed insole innovation significantly reduced numbness in both feet among individuals with type 2 diabetes. These findings support the potential integration of this innovation into existing diabetic foot care regimens, potentially contributing to the prevention of foot ulcers and lower-limb amputations. Further research involving larger sample sizes and extended follow-up is recommended to confirm these results and assess long-term outcomes. Keywords: palm seed insole; diabetic neuropathy; foot numbness; reflexology; innovation; monofilament